Mahalnya Ongkos Politik dalam Pemilu Serentak Tahun 2019 - Sholikin, Ahmad (Faculty of Social and Political Science Universitas Brawijaya, 2019)
The amount of money circulating in the 2019 Election has the potential to increase from the 2014 general election. This is based on several things. First, the system and mechanical elections have not changed from 2014. This means that the personal side or orientation of the election competition is still based on legislative candidates rather than political parties. Second, the orientation of the 2019 Legislative Election competition remains based on the popularity and personality of candidates. Third, to be elected, every legislative candidate will still try to increase its popularity, increase campaign activities, and personally finance it. In Indonesia, one of the crucial topics in each general election is about money management in elections. The role and function of money in elections is very important in studies in the social sciences, especially political science, law, and economics. This issue then brings various consequences for election participants, election organizers, and from the voter side so that the phenomenon of the widespread practice of money politics is also a major issue in the implementation of each election.